Cycled training service for 9-10 year old crawl swimming groups: harmonized technical and physical progress model - Ponimasov, O. E.; Ryabchuk, V. V.; Titarenko, Yu. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop and test benefits of a new harmonized technical and physical fitness model (also referred to as the combined training technology) in application to junior (9-10 year old) crawl swimmers.